A Comparative survey of proboscis and tymbal morphology in Tiger moths (lepidoptera: erebidae: arctiini) - Coy, Stacey L. (My University, 2016)
Arctiini (tiger moths) include some of the most brightly colored, charismatic moths in the order Lepidoptera. Bright coloration and sound production in tiger moths can serve as defense mechanisms to warn predators of their unpalatability. In some arctiines, atypical adult feeding behaviors have been documented, including obtaining secondary plant compounds for chemical protection rather than nutrition, a.k.a. pharmacophagy. Tiger moth species have also been recorded warning bat predators of their distastefulness by producing sound with specialized structures. Other tiger moths are palatable, and use sound to jam bat sonar, thereby evading predation. Previous morphological work has demonstrated an association between some adult feeding behaviors and uniquely specialized proboscis sensory structures. Whether adult pharmacophagous tiger moths have specialized structures for pharmacophagy was previously unknown. I hypothesized there is a connection between the number of proboscis sensory structures, adult pharmacophagy and phylogeny in arctiines. My results demonstrate that individuals known to sequester pyrrolizidine alkaloids (PA’s) as adults have more proboscis sensilla on average than those that do not sequester PA’s as adult, but are PA feeders as larvae. Some tiger moths have developed a secondary organ, the tymbal, for defense through ultrasonic sound. Little morphological work has been done to examine tymbal microstructure; however, some evidence suggests variation in tymbal size between tiger moth species. I predicted there is a correlation between the surface area of the tymbal and specific defensive behaviors (e.g., acoustic aposematism vs. jamming). Results from my morphological surveys provided new character states for comparative evolution analyses within a phylogenetic framework. Further, this work has predictive power providing valuable insight into unknown species behaviors, and can inform future studies in chemical ecology and behavior.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science - Biology
Keywords: Lepidoptera; Moths; Tiger moths